Becoming Authentic Teachers Through Transformative Inquiry: Final Practicum Challenges - Tse, Vanessa; Abra, Meaghan; Tanaka, Michele (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2017)
Within the final teaching practica, pre-service teachers encounter the crucial challenge of redefining their teacher identities. Leaving behind personas formed as students, professional settings necessitate asking themselves what kind of teacher they want to be in a new context. In collaboration with their professor, two pre-service teachers examined their final practicum experiences, highlighting how Transformative Inquiry (TI), a holistic investigative approach, supported them in becoming authentic teachers. We hear how the TI process helped them identify, honour, and strengthen their personal and unique teaching identities. Highlighted themes include: touchstone stories, the power of the circle, living the questions, and the importance of on-going reflection. These new teachers resisted traditional images of teachers by embracing imperfection and vulnerability.